2014
DOI: 10.5858/arpa.2012-0493-ra
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Cervical Glandular Neoplasia and Issues in Differential Diagnosis

Abstract: Clinical and morphologic features as well as immunohistochemistry results should be used in conjunction in the differential diagnosis of glandular proliferations of the cervix, as correct interpretation has major clinical consequences for the patient in most instances (especially benign versus malignant). Immunohistochemical markers should be used as part of a panel of antibodies, as exceptions may occur to the usual pattern of staining, and if used singly, they may mislead the pathologist to establish a wrong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 285 publications
0
43
0
1
Order By: Relevance
“…It is well recognised that the distinction of endocervical and endometrial carcinoma can be problematic even on biopsy material, sometimes necessitating additional immunohistological studies for resolution. 17 We found that the risk of high-grade cervical dysplasia was greater in younger women (aged 25-34 years), and in those with no cervical screening history or a previously detected low-grade cytological abnormality. In contrast, there was no correlation with socio-economic status or with access to services.…”
Section: Discussionmentioning
confidence: 68%
“…It is well recognised that the distinction of endocervical and endometrial carcinoma can be problematic even on biopsy material, sometimes necessitating additional immunohistological studies for resolution. 17 We found that the risk of high-grade cervical dysplasia was greater in younger women (aged 25-34 years), and in those with no cervical screening history or a previously detected low-grade cytological abnormality. In contrast, there was no correlation with socio-economic status or with access to services.…”
Section: Discussionmentioning
confidence: 68%
“…2A, C) may raise the possibility of an invasive ENDO-CA or EM-CA. [26][27][28] In contrast, some EM-CAs may invade the cervical stroma and undermine normal endocervical glands with little in the way of a stromal response, closely mimicking MRs or MHs. 29 Rarely, MCAs may arise as primary neoplasms in the wall of the uterine corpus (2 cases included in this study; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Microglandular hyperplasia of the endocervix is a localized non-neoplastic proliferation of the glandular epithelium of the endocervix. Although these growths may show architectural or cytological abnormalities, they differ from malignant tumours, and can easily be misinterpreted as pre-malignant or malignant neoplasms of the endocervix [9][10][11]. Microglandular hyperplasia is found most commonly in younger women (between the ages of 25-37) and is often an incidental microscopic finding [12,13], is just like adenocarcinoma of the endometrium, associated with endogenous hormones, and induced by pregnancy hormones, gynecological therapeutic treatments or through oral contraceptive therapy [6,7,14].…”
Section: Discussionmentioning
confidence: 99%